Is innovation (increasingly) concentrated in large cities? An international comparison - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2020)
We investigate the geographic concentration of patenting in large cities using a sample of 14 developed countries. There is wide dispersion of the share of patented inventions in large metropolitan areas. South Korea and the US are two extreme outliers where patenting is highly concentrated in large cities. We do not find any general trend that there is a geographic concentration of patents for the period 2000-2014. There is also no general trend that inventors in large cities have more patents than in rural areas (scaling). Hence, while agglomeration economies of large cities may offer advantages for innovation activities, the extent of these advantages is not very large. We conclude that popular theories over-emphasize the importance of large cities for innovation activities.
Keywords: O31; R12; O57; 330; Innovation; patents; cities; urban scaling; creativity